Religious studies for A-level year 1 and AS - Frye, John (AQA A-level religious studies, 2017)
AQA ApprovedEngage students with accessible content that draws out the key theories, ensuring students have a thorough understanding of Christianity and the philosophical and ethical issues; developed by subject specialist John Frye and the leading Religious Studies publisher*.- Confidently teach 'Philosophy and religion' and 'Ethics, religion and society' with comprehensive coverage of the key philosophers, concepts and theories along with sources of theological authority- Supports learning and revision with a range of contemporary activities, discussion points and unit summaries- Prepares students for assessment with revision questions at the end of each chapter and practice questions tailored to the assessment objectives. Content covered:Philosophy and religion Sections A and B (Section A is covered through Christianity)Ethics, religion and society Sections A and B (Section A is covered through Christianity) Free support- Sample material for Book 2 - Summer term 2017All of the above will be available online at www.hoddereducation.co.uk/alevelrs/aqa *Taken from Educational Publishers Council statistics